Systemic inflammatory markers in neuropathic pain, nerve injury, and recovery. Issue 3 (March 2022) - Sandy-Hindmarch, Oliver; Bennett, David L.; Wiberg, Akira; Furniss, Dominic; Baskozos, Georgios; Schmid, Annina B.
Abstract : Abstract: The role that inflammation plays in human nerve injury and neuropathic pain is incompletely understood. Previous studies highlight the role of inflammation in the generation and maintenance of neuropathic pain, but the emerging evidence from the preclinical literature for its role in the resolution of neuropathic pain remains to be explored in humans. Here, we use carpal tunnel syndrome (CTS) as a human model system of nerve injury and neuropathic pain to determine changes in serum cytokine protein levels and gene expression levels before (active stage of disease) and after carpal tunnel decompression surgery (recovery). Fifty-five patients with CTS were studied, and 21 healthy age-matched and gender-matched participants served as controls. In the active stage of the disease (CTS before surgery vs healthy controls), PTGES2 mRNA was decreased in patients (adjusted P = 0.013), while transforming growth factor-β and C-C motif chemokine ligand 5 protein levels were increased (adjusted P = 0.016 and P = 0.047, respectively). In the resolution phase (CTS before surgery vs after surgery), IL-9 mRNA was increased after surgery (adjusted P = 0.014) and expression of IL-6 mRNA and IL-4 protein levels were increased before surgery (adjusted P = 0.034 and P = 0.002, respectively). IL-9 mRNA expression negatively correlated with several (neuropathic) pain scores. By contrast, protein levels of IL-4 positively correlated with pain scores. In conclusion, we demonstrate specific dysregulation of systemic cytokine expression in both the active and resolution phases of nerve injury and neuropathic pain. IL-9 represents an interesting candidate associated with resolution of nerve injury and neuropathic pain. Abstract : Supplemental Digital Content is Available in the Text.Systemic inflammatory mediators are dysregulated in both the active and resolution phases of nerve injury and relate to neuropathic pain.